Effects of cluster headache preventatives on mouse hypothalamic transcriptional homeostasis. (July 2022) - Pistolesi, Alessandra; Buonvicino, Daniela; Muzzi, Mirko; Urru, Matteo; Chiarugi, Alberto
Objective: To investigate how cluster headache preventatives verapamil, lithium and prednisone affect expression of hypothalamic genes involved in chronobiology. Methods: C57Bl/6 mice were exposed to daily, oral treatment with verapamil, lithium, prednisone or amitriptyline (as negative control), and transcripts of multiple genes quantified in the anterior, lateral and posterior hypothalamus. Results: Verapamil, lithium or prednisone did not affect expression of clock genes of the anterior hypothalamus ( Clock, Bmal1, Cry1/2 and Per1/2 ). Prednisone altered expression of hypothalamic neuropeptides melanin-concentrating hormone and histidine decarboxylase within the lateral and posterior hypothalamus, respectively. The three preventatives did not affect expression of the neurohypophyseal hormones oxytocin and arginine-vasopressin in the posterior hypothalamus. Conversely, amitriptyline reduced mRNA levels of Clock, oxytocin and arginine-vasopressin. Conclusion: Data suggest that cluster headache preventatives act upstream or downstream from the hypothalamus. Our findings provide new insights on hypothalamic homeostasis during cluster headache prophylaxis, as well as neurochemistry underlying cluster headache treatment.